2006
DOI: 10.2170/physiolsci.rp005306
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Arrhythmia and Nausea of Motion Sickness Induced in Healthy Japanese Subjects Viewing an Optokinetic Rotating Drum

Abstract: Abstract:The purpose of this study was to investigate whether nausea or gastric dysrhythmia, including tachygastria, which was determined by electrogastrography (EGG), were observed during optokinetic motion sickness in healthy Japanese volunteers. Twelve volunteers (9 men and 3 women) participated in the study. The subjects were asked to sit in a chair with their heads positioned in the center of a drum whose inside had been painted with black and white stripes. After a 15 min resting period, the drum was rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Imai K et al . founded an increase in tachygastria accompanied with a decrease in the percentage of normal slow waves induced by optokinetic motion sickness . Chen et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Imai K et al . founded an increase in tachygastria accompanied with a decrease in the percentage of normal slow waves induced by optokinetic motion sickness . Chen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Imai K et al founded an increase in tachygastria accompanied with a decrease in the percentage of normal slow waves induced by optokinetic motion sickness. 28 Chen et al reported that audio stimulation (noise) decreased percentage of normal gastric slow wave in adolescents in fasting state. 29 In addition, there was a significant increase in the instability coefficient of dominant frequency with the cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…The visual stimuli decreased the percentage of normal slow waves in the fasting state, attributed to an increase in bradygastria and tachygastria. The effect of stress on gastric slow waves was shown by Imai et al 32 who demonstrated an increase in tachygastria with a decrease in the normal slow waves induced by optokinetic motion sickness. Also, Chen et al 33 showed that audio stimulation (noise) impaired percentage of normal gastric slow wave in adolescents.…”
Section: Discussionmentioning
confidence: 88%
“…All participants' palates were cleaned first, followed by their tongues. After cleaning, the participants rated the extent of nausea they felt using a visual analogue scale (VAS) [15], which ranged from 0 (not at all) to 10 (very strong). To rule out the effect of cleaning time on nausea, we measured it using a stopwatch from mouth opening to mouth closing.…”
Section: Measurement Of Nausea Extent Caused By Coronal and Sagittal mentioning
confidence: 99%